Diagnostic Value of Endoscopic Ultrasonography for Common Bile Duct Dilatation without Identifiable Etiology Detected from Cross-Sectional Imaging - Nonthalee Pausawasdi; Penprapai Hongsrisuwan; Lubna Kamani; Kotchakon Maipang; Phunchai Charatcharoenwitthaya (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Endoscopic ultrasonography (EUS) is warranted when cross-sectional imaging demonstrates common bile duct (CBD) dilatation without identifiable causes. This study aimed to assess the diagnostic performance of EUS in CBD dilatation of unknown etiology. Methods Retrospective review of patients with dilated CBD without definite causes undergoing EUS between 2012 and 2017. Results A total of 131 patients were recruited. The mean age was 63.2±14.1 years. The most common manifestation was abnormal liver chemistry (85.5%). The mean CBD diameter was 12.2±4.1 mm. The area under the receiver operating characteristic curve (AUROC) of EUS-identified pathologies, including malignancy, choledocholithiasis, and benign biliary stricture (BBS), was 0.98 (95% confidence interval [CI], 0.95-1.00). The AUROC of EUS for detecting malignancy, choledocholithiasis, and BBS was 0.91 (95% CI, 0.85-0.97), 1.00 (95% CI, 1.00-1.00), and 0.93 (95% CI, 0.87-0.99), respectively. Male sex, alanine aminotransferase ≥3× the upper limit of normal (ULN), alkaline phosphatase ≥3× the ULN, and intrahepatic duct dilatation were predictors for pathological obstruction, with odds ratios of 5.46 (95%CI, 1.74-17.1), 5.02 (95% CI, 1.48-17.0), 4.63 (95% CI, 1.1-19.6), and 4.03 (95% CI, 1.37-11.8), respectively. Conclusions EUS provides excellent diagnostic value in identifying the etiology of CBD dilatation detected by cross-sectional imaging.